Censoring the body - Lucie-Smith, Edward (London, UK : Seagull Books, 2007)
"From the earliest times, human beings have found it difficult to represent their own bodies in a straightforward way. At the dawn of art, representations of the nude body focused almost entirely on fertility, with some cultures explicit and others rather more prudish about representing the unclothed body. With the coming of Christianity, representations of the nude became associated with the idea of the Fall of Man and original sin. This conflicted with the need to show nude or nearly nude bodies when representing episodes from the Passion of Christ and the martyrdoms of popular saints." "Today, representations of the nude remain a battleground, fought over by libertarians and anti-libertarians. Most recently, feminism has challenged images of the female nude, while an increasing moral panic now restricts the depiction of the naked child - images which would have been commonplace in the art of the Renaissance." "Censoring the Body exposes our bodies and our ideas about our bodies, revealing the complex historical and cultural legacies which frame - and obscure - our vision."--BOOK JACKET.
Series created in collaboration with the Index on censorship.
Keywords: Nude in art -- History; Nude in art -- Censorship -- History